Important computer competencies for the nursing profession. - Jiang W; Chen W; Chen Y (Journal of Nursing Research (Taiwan Nurses Association), 2004)
Nursing requires computer competencies. This study aimed at identifying those competencies required for the nursing profession in Taiwan. The Delphi technique was deployed in this study. In the Delphi questionnaires, computer competencies were sorted into seven domains: concepts of hardware, software, and networks; principles of computer applications; skills of computer usage; program design; limitations of the computer; personal and social issues; attitudes toward the computer. In three Delphi questionnaires, nursing informatics experts gave us their opinions on the importance of each computer competency for the nursing profession. The experts also designated when the competency should be cultivated. This study provides a comprehensive list for nursing professionals to check on their computer competence. The results of this study should also serve as good references for teachers and schools in designing related curriculums.